Preparedness of recovery to the vulnerability of climate change in the coastal areas in Bangladesh - Rokonuzzaman, Mohammed; Hattori, Yuta (Innovation Journal of Social Sciences and Economic Review, 2021)
The purpose of this study is to assess the vulnerability of Bangladesh’s coastal areas to natural disasters driven by climate change and to evaluate the effectiveness of current coping mechanisms. The research involved surveying farmers across eight coastal unions, focusing on their socio-economic characteristics, family size, income levels, and the impact of climate change on their livelihoods. The study employed a mixed-methods approach, utilizing face-to-face interviews, in-depth case studies, and focus group discussions to gather both qualitative and quantitative data. The findings indicate that Bangladesh’s coastal regions are highly susceptible to climate-related disasters, particularly cyclones and flooding, which exacerbate socio-economic challenges. The study reveals that existing shelters are inadequate for the dense population, a situation further complicated by the COVID-19 pandemic, which increases the vulnerability of affected communities. Coping mechanisms, such as rainwater and groundwater storage and women’s involvement in dairy production, have shown some effectiveness in sustaining household income. However, these measures are insufficient to fully mitigate the impacts of climate change. The study concludes that adaptation strategies focusing on accommodation and protection are crucial, given Bangladesh’s high population density and limited resources for retreat. The implications of this research suggest that enhancing these adaptation strategies through need-based training and improving infrastructure could significantly bolster the resilience of coastal communities. Furthermore, there is a pressing need for international support to address the broader challenges posed by climate change, particularly in safeguarding the Sundarbans’ biodiversity and the livelihoods of millions in coastal areas.